Thailand Economic Monitor 2016 : Services as a New Driver of Growth - World Bank Group (World Bank, Bangkok, 2019)
Economic growth is expected to attain 3.1 percent in both 2016 and 3.2 percent in 2017 accelerating from 2.8 percent last year with private consumption and public investment as key drivers as consumer sentiment recovers, households deleverage and large public infrastructure projects are implemented. The Thai economy decelerated to 3.2 percent in 2016Q3 compared to 3.5 percent in Q2 as public spending, private investment and private consumption slowed. A frm recovery has yet to take hold amid a slowdown in domestic demand in 2016Q3. Major drivers of growth associated with economic recovery such as private consumption and private investment have yet to show a broad-based and sustained expansion. Public spending and private consumption are projected to underpin growth in 2017 with headwinds from more uncertain global economic prospects. Continued commitment to implementing structural reforms is critical to raising the long-term growth path.